Expression of OCT4 isoforms is reduced in primary colorectal cancer - Turyova, Eva; Mikolajcik, Peter; Grendar, Marian; Kudelova, Eva; Holubekova, Veronika; Kalman, Michal; Marcinek, Juraj; Hrnciar, Matej; Kovac, Michal; Miklusica, Juraj; Laca, Ludovit; Lasabova, Zora (Frontiers in Oncology, 2023)
Colorectal cancer (CRC) is one of the most common types of cancer worldwide. The carcinogenesis of CRC is indeed complex and there are many different mechanisms and pathways that contribute to the development of malignancy and the progression from primary to metastatic tumor. The OCT4A, encoded by the POU5F1 gene, is transcription factor responsible for the phenotype of stem cells, maintaining pluripotency, and regulation of differentiation. The POU5F1 gene is made up of five exons that can through alternative promotor or alternative splicing, create numerous isoforms. In addition to OCT4A, other isoforms called OCT4B are also translated into protein, however, their role in cells has been unclear. The aim of our work was to investigate the expression patterns of OCT4 isoforms in primary and metastatic CRC, providing us with useful information about their role in the development and progression of CRC. Surgical specimens from overall 78 patients were collected and isolated from primary tumors (n = 47) and metastases (n = 31). The relative gene expression of OCT4 isoforms was investigated using the RT-qPCR method together with TaqMan probes specific for particular OCT4 isoforms. Our results suggest significantly downregulated expression of the OCT4A and OCT4Bs isoforms in both primary (p=0.0002; p<0.0001, resp.) and metastatic tumors (p=0.0006; p=0.00051, resp.) when compared to control samples. We also observed correlation between reduced expression of all OCT4 isoforms and both primary and left-sided tumors (p=0.001; p=0.030, resp.). On the other hand, the expression of all OCT4 isoforms was significantly upregulated in metastases compared to primary tumors (p<0.0001). Unlike previous reports, we found out that the expression of OCT4A, OCT4Bs and all OCT4 isoforms is significantly reduced in primary tumors and metastases compared to control samples. On the other hand, we suppose that the expression rate of all OCT4 isoforms may be related to the cancer type and side, as well as to liver metastases. However, further studies are required to investigate the detailed expression patterns and significance of individual OCT4 isoforms in carcinogenesis.